2013
DOI: 10.1111/j.1747-4477.2009.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of soft tissue examination in post‐traumatic decision‐making: A case report

Abstract: Dental and facial traumas involving teeth and supporting tissues are common sports-related injuries. In this case report treatment of a 23-year-old student who had been elbowed by an opponent player during a basketball game, which caused oblique fractures on both maxillary incisor teeth is presented. The patient presented 17 days following trauma having completed full recovery of soft tissues. A fragment of upper incisor tooth had been embedded in lower lip at the time of trauma, which was covered by healing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It has been reported that these injuries occur in association with soft tissue lacerations; as a result, the embedding of the fractured tooth fragment in the surrounding soft tissues is a common sequela. [123] An extensive review of PubMed literature revealed reports of tooth fragments embedded in various soft tissues [Table 1]. [123] Among these, in most of the reported cases (16 out of 24 case reports), the lower lip was the most common site for the embedded incisor fragment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that these injuries occur in association with soft tissue lacerations; as a result, the embedding of the fractured tooth fragment in the surrounding soft tissues is a common sequela. [123] An extensive review of PubMed literature revealed reports of tooth fragments embedded in various soft tissues [Table 1]. [123] Among these, in most of the reported cases (16 out of 24 case reports), the lower lip was the most common site for the embedded incisor fragment.…”
Section: Discussionmentioning
confidence: 99%
“…[123] An extensive review of PubMed literature revealed reports of tooth fragments embedded in various soft tissues [Table 1]. [123] Among these, in most of the reported cases (16 out of 24 case reports), the lower lip was the most common site for the embedded incisor fragment. [1,3,4,9,1117,19,20,22,23] However, Kalra et al ,[10] Cubukcu et al ,[18] and Agarwal et al [2] reported cases with tooth fragments embedded in the upper lip.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to transfer the fractured fragments in aqueous transport mediums such as normal saline until reattachment occurs. Interestingly, soft tissue of lips may act as a physiologic medium for tooth fragments as reported in late presentations [10,14].…”
Section: Discussionmentioning
confidence: 99%